Captain Underpants and the preposterous plight of the purple potty people : the eighth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2006)
When George and Harold use their traveling purple potty to travel to another dimension where the school is nice and the principal, Mr. Krupp, thinks they're funny, they meet up with their evil twins and must face their cleverest enemies ever -- themselves.
1. George and Harold -- 2. Those Wacky Grown-Ups -- 3. The School of Hard Knocks -- 4. Purple Pottyville -- 5. Strangers in Paradise Lost -- 6. The World According to George -- 7. Gettin' Outta Town -- 8. The Preposterous Plight of Captain Blunderpants -- 9. Not Without My Hampster (... and My Pterodactyl) -- 10. Hypno-Horror -- 11. Cracker to the Rescue -- 12. Ka-Blamski! -- 13. Purple Potty People Unite! -- 14. The Chapter Where Some Stuff Happens -- 15. Super Supper -- 16. The Adventures of Boxer Boy and Great-Granny Girdle -- 17. Meanwhile, Back at the Tree House -- 18. Crash! -- 19. Whenhamstersattack.com -- 20. The Incredibly Graphic Violence Chapter, Part 1 (in Flip-O-Rama) -- 21. The Anti-Climactic Chapter -- 22. Ka-Boom! -- 23. Two Minutes Later ... -- 24. Nobody Messes With Our Grandbabies! -- 25. The Incredibly Graphic Violence Chapter, Part 2 (in Flip-O-Rama) -- 26. Shrinky-Dorks -- 27 The Incredibly Graphic Violence Chapter Part 3 (in Flio-O-Rama -- 28. Wrapping Things Up -- 29. To Make a Long Story Short -- 30. To Make a Longer Story Even Shorter -- 31. The Chapter Where Nothing Bad Happens -- 32. The Thing That Could Be Worse Than Going to Jail for the Rest of Their Lives.
Accelerated Reader
Keywords: School principals -- Juvenile fiction; Heroes -- Juvenile fiction; Science fiction; Humorous stories; Schools -- Juvenile fiction; Schools -- Fiction; School principals -- Fiction; Heroes -- Fiction; Cartoons and comics -- Fiction; Humorous stories; Heroes and heroines -- Juvenile fiction; Graphic novels -- Juvenile fiction; School stories -- Juvenile fiction; Graphic novels; Humorous fiction; Humorous fiction; Humorous stories -- Juvenile